“Le madri sono l’albero della nave”: cuidados, sentimentos e poder materno nas famílias de mercadores e banqueiros da Florença do Quattrocento - Fallabrino, Maria Verónica Perez (2020)
The purpose of this thesis is to analyze motherhood among the merchants and bankers’ families of Quattrocento’s Florence, aiming to understand mainly, what it meant to be a mother in these families and to define how the mother's function and affection were lived and understood within this group of the society. Based on humanistic and religious treaties and personal sources (letters and family diaries), we seek to understand the meaning of motherhood and its function for the family and society, considering the ideals and representations disseminated in the Florentines´ personal records and in the treatises on family life written at the time. Furthermore, from the individual experiences narrated in the documents, to define what represented “being a mother” in terms of the various subjects that involved raising children: education, care, protection, advice, reprimands, support, transmission of values and attention to the family. Likewise, we consider the “feeling of mother” in the letters that women wrote to their children, considering the attitudes, feelings, emotions and expressions of affection they expressed in the various experiences and moments of family life, without forgetting the reciprocity of the relationship. of mothers and children, exposing how they expressed their feelings and care and how they corresponded to maternal affection and guidance